Case report: a cataract induced by bleomycin in a patient with testicular cancer - Zhang, Wan; Ji, Yinghua; Sun, Yufei; Zhi, Keya; Yang, Han; Zhang, Min; Lu, Ping; Zhang, Yana (Frontiers in Pharmacology, 2024)
Background: Bleomycin is a glycopeptide antibiotic with outstanding anti-tumor effects. A major adverse effect of bleomycin is lung fibrosis. However, the development of cataracts as a severe adverse effect has not been reported.Case summary: Herein, we describe the first case of cataract induced by bleomycin therapy in a 22year-old male with testicular cancer. After surgical intervention and following five successive chemotherapy cycles of the BEP regimen, including bleomycin, etoposide and cisplatin, the patient reported a gradual painless loss of vision, with substantial decline in visual ability, especially in the right eye. Following comprehensive eye examinations, a cataract was diagnosed. Eventually, the patient underwent phacoemulsification and received replacement of the intraocular lenses.Bleomycin can cause cataracts, which induces a significant loss of vision. Therefore, clinicians should observe early symptoms and properly adjust treatment to prevent aggravation of symptoms.